PROFIL IBU RUMAH TANGGA YANG BEKERJA SEBAGAI PENYAPU JALAN DI KOTA PEKANBARU - Dessy Ariza; M. Razif " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This research was conducted to find out how the recruitment process and the factors that influence the Housewife chose to work as a street sweeper in Pekanbaru. Where in this Pekanbaru City street sweeper more women than men. To find out how the recruitment process and factors such mempengaruhui Housewife chose to work as a street sweeper in Pekanbaru, the authors conducted data collection by using the technique of direct interview with the respondents using a list of questions prepared in advance, and also that researchers obsevarsi directly observing the behavior of the respondent. Using purposive sampling technique that researchers have determined the subject of research with the assumption or opinion of himself as a subject research. Results of research conducted that the recruitment process Housewife be a street sweeper in Pekanbaru is relatively easy because the terms are defined not difficult to include are: photocopy KK (family card), a copy of ID card (Identity Card), and a cover letter. Street sweeper is supervised by a foreman at each working area, street sweeper was divided into two, namely: sweeper median (1), sweeper sand (2). The median is the sweeper sweeping trash system with the middle area of the road that separates the space between the right and left of the road, while the sweeper sand or so-called sweeper edge is swept trash system aupun sand with right or left area roads. The husband's income is not sufficient is one of the factors that affect their work as a street sweeper. Allocation of their income to meet their child's school fees in addition to working as a street sweeper they can meet the needs of themselves without having to like buying clothes, veil, powder, and else.Keywords : Motivation , Status and Role , Women and Work